Characterization of chlorobenzoate degraders isolated from polychlorinated biphenyl-contaminated soil and sediment in the Czech Republic - Pavlû, L; Vosáhlová, J; Klierová, H; Prouza, M; Demnerová, K; Brenner, V (Journal of applied microbiology, 1999)
Two polychlorinated biphenyl-contaminated sites in the Czech Republic, a soil at Zamberk and a sediment sludge at Milevsko, were screened for the presence of chlorobenzoate degraders. Sixteen different chlorobenzoate degraders were isolated from the soil compared with only three strains isolated from the sediment. From these strains, only four soil degraders and one strain isolated from the sediment, respectively, were shown to possess a complete chlorobenzoate (CB) pathway. Bacteria isolated from the soil have expressed more flexibility for CB degradation, namely in the case of ortho-chlorinated benzoates. They all possessed large plasmids, the restriction patterns of which were compared. Plasmids in Pseudomonas sp. A7, A8, A18 and A19, respectively, were cured and found to encode at least part of the metabolic pathway involved in the growth on ortho-chlorinated benzoates.
Keywords: biodegradace; látky znečišťující půdu; Czech Republic; katechol-1,2-dioxygenasa; plazmidy; Pseudomonas; Plasmids; Soil Microbiology; oxygenasy; DNA bakterií; Chlorobenzoates; Polychlorinated Biphenyls; chlorbenzoáty; Česká republika; dioxygenasy; DNA, Bacterial; půdní mikrobiologie; Catechol 1,2-Dioxygenase; polychlorované bifenyly; Dioxygenases; Oxygenases; Biodegradation, Environmental; Soil Pollutants